“To Europe together with Russia”: Ukrainian foreign policy during Leonid Kuchma’s presidency (Economic and Political Thought, 2018)
The present paper discusses the following research questions: To whatextent did President Kuchma’s mistakes made during his final presidencyhave impact on Ukraine’s inability to conduct systemic reforms (e.g. combatingcorruption, development of the foundations for a stable state based onthe rule of law with free market economy)?, Can it be stated that the lackof radical reforms and mistakes in Ukraine’s foreign policy during Kuchma’sfinal presidency contributed to the outbreak of the Orange Revolution, andalso enabled Viktor Yanukovych to take leadership and in fact resulted inthe Euromaidan? Can the final stage of Kuchma’s presidency (2001–2004),especially in terms of foreign policy, be characterised as multi-directionalwith the emphasis on the rapprochement with Russia?
Keywords: Ukraine, Ukraine’s foreign policy, the European Union, democracy